Uma abordagem sistemática em espécies de astyanax (characiformes, characidae, incertae sedis) da bacia do alto-médio rio Uruguai através da análise citogenética básica e molecular - Gavazzoni, Mariane (2016)
Astyanax is a polyphyletic taxon with richness of species and wide geographic distribution. Astyanax comprises species that are morphologically very similar with poorly detailed taxonomic delimitations, which makes it difficult to identify and to establish phylogenetic relationships. In order to provide data to contribute to cytogenetic, taxonomy and systematics of Astyanax, cytogenetics analyzes were carried out on ten Astyanax species from three river basins. Astyanax altiparanae and A. aff. fasciatus were collected on the Upper Paraná River basin; A. abramis and A. asuncionensis were collected on the Middle-low Paraná River basin; and A. cf. aramburui, A. eigenmanniorum, A. aff. fasciatus, A. jacuhiensis, A. aff. laticeps, A. cf. paris and Astyanax sp. were collected on the Upper-Middle Uruguai River basin. The results show interespecific variation in diploid number, 2n=46 chromosomes for A. cf. aramburui and A. aff. fasciatus, 2n=48 chromosomes for A. eigenmanniorum, and 2n=50 chromosomes for the remaining species. NORs (Ag-staining and 18S rDNA-FISH) showed species bearing single sites and species bearing multiple sites (up to 10 cistrons in Astyanax sp.), confirming the high variability reported for the genus. The species from A. bimaculatus complex (A. abramis, A. altiparanae, A. jacuhiensis e A. asuncionensis) showed single NORs, a plesiomorphic condition for the complex. FISH with 5S rDNA probes revealed a more conserved condition, with centromeric sites in at least one metacentric chromosome pair and one subtelocentric/acrocentric chromosome pair, however with interspecific variation, which proves it to be an important marker in the characterization and differentiation of these species. Heterochromatin distribution pattern was distinct for all species, except for A. cf. aramburui and A. aff. fasciatus (Ijuí River). This demonstrates that cytogenetic similarities may indicate closer relationship between each other than among to the other analyzed species; on the other hand, 5S rDNA genes showed to be important in differentiation of these cryptic species. The results reported the first cytogenetic data for A. cf. paris and reinforce their cytogenetic similarity with other congenus species, and we also report the occurrence of a Astyanax species that has not been taxonomically described yet. Thus, the results of this study provide data that assist taxonomy and systematic of Astyanax clade and Astyanax paris clade , reinforcing the need for extensive revisions, especially in A. bimaculatus and A. fasciatus complex, including markers such as 5S rRNA and heterochromatin distribution pattern, forthe better understanding of the phylogenetic relationships in Astyanax.